2018
DOI: 10.1371/journal.pone.0199624
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) prevalence and associated risk factors in women from Curaçao

Abstract: BackgroundIn the Caribbean region, a notable difference in HPV-prevalence and genotypes distribution between the islands is observed. Recently we found in Curaçao a low incidence of HPV16 and 18 in cervical cancer compared to the standard world population. We aimed to determine HPV-prevalence, HPV-genotype distribution and associated risk-factors in women from Curaçao.Methods5000 women aged 25–65 years were randomly selected from the national Population Register. HPV was detected by means of GP5+/6+PCR EIA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
(18 reference statements)
3
14
0
Order By: Relevance
“…The large sample sizes enable precise estimates of both increases and decreases in HPV type specific prevalence, which could be used as a baseline for comparison to future samplings of the population. The overall prevalence of HPV DNA in this representative sample of women was 18.71%, with the highest prevalence (33.11%) among women aged less than 21 years, corresponding with the data reported by Curacao (19.7%) [15]. Global HPV prevalence estimates are well-known to vary by the region, study design, target population and calendar time [16].…”
Section: Discussionsupporting
confidence: 78%
“…The large sample sizes enable precise estimates of both increases and decreases in HPV type specific prevalence, which could be used as a baseline for comparison to future samplings of the population. The overall prevalence of HPV DNA in this representative sample of women was 18.71%, with the highest prevalence (33.11%) among women aged less than 21 years, corresponding with the data reported by Curacao (19.7%) [15]. Global HPV prevalence estimates are well-known to vary by the region, study design, target population and calendar time [16].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, HPV infections were significantly region‐specific . One study in Beijing showed that the overall HPV infection rate was 6.7%, and the infection rate of cervical HPV infections in women without cytological abnormalities was only 4.8% .…”
Section: Discussionmentioning
confidence: 99%
“…A striking finding of this study was that less than one third of GPs interviewees stated that they often or always collect information on the sexual habits of 12–26 years’ girls and boys. It is worth mentioning that GPs should be aware of population groups at risk for unhealthy sex life habit since such behavior plays an important role in the process of high-risk HPV persistent infection for adolescents and young adults [ 20 , 21 , 22 ]. Therefore, it is important to know the adolescent’s sexual habits in order to prioritize preventive strategies and to develop educational campaigns that should be routinely conducted to prevent the spread of HPV.…”
Section: Discussionmentioning
confidence: 99%